Inflammation and Cardiovascular Disease - R. Hadi, Najah; M. Muhammad-Baqir, Bashaer; H. Ahmed, Mustafa (Inflammatory Response to Percutaneous Coronary Intervention, 2021)
Cardiovascular disease is the leading cause of death in the all world. One of its most important forms is coronary heart disease due to atherosclerosis. There is increasing evidence that inflammatory system has a role in the pathogenesis of cardiovascular disease and its complications. Inflammatory mechanisms also appear to determine clinical presentation and disease outcome. Plasma levels of several markers of inflammation has been associated with coronary artery disease and various studies have shown increased levels during chronic stable angina, acute myocardial infarction, and percutaneous coronary intervention and have been found to be associated with future cardiovascular risk in a variety of clinical settings.